Whisteblowing intentions in the retaliation sphere / Shahriza Ilyana Ramli and Azni Syafena Andin Salamat - Ramli, Shahriza Ilyana; Andin Salamat, Azni Syafena (Universiti Teknologi MARA, Kedah, 2013)
‘Whistleblowing’ – the word started to be known in 1970s. In Malaysia, the act pertaining this matter has been enforced on 15th December 2010 by its name Whistleblower Protection Act 2010, under the Act 117. The need to establish this act is seen after several initiatives and programmes handled by government to uphold the public administration in Malaysia have failed to give any significant impact. After all, the wrongdoings are still happening at an alarming stake. To note, the act pertaining whistleblowing has been passed by parliament in the measurement taken against corruption cases which as one of the focus under second thrust of New Key Result Area (NKRA) which is to combat the corruption in Malaysia with the hope that indirectly, it will help attaining the first thrust of NKRA which is to eventually reduce the criminal rate in Malaysia. This paper attempts to discuss the retaliation sphere towards whistleblowing intentions in an organizational setting. The research is conducted among 80 respondents from one of the tertiary education institutions in Malaysia. Thus, with this research it is hope that it would be a drive towards establishing ethical culture among public servants to blow the whistle if they found any wrongdoings happend in their surroundings.